Are Libraries Necessary? Are Libraries Obsolete? - Silka, Linda; Rumery, Joyce (Maine Policy Review, 2013)
Libraries are under siege. They face competing demands not only from different people but also from the same people at different times. Some assert that libraries must continue to strengthen their role as physical centers at the heart of their communities. Others argue that the future of libraries is at the leading edge of the revolution in digital information technologies. The authors introduce this special issue of Maine Policy Review on libraries and information. They provide an overview of the importance and complexity of the issues underlying these varying visions for how Maine libraries should serve their communities in the coming years.